Validation of four AIDS-case definitions in HIV-infected intravenous drug users in Barcelona, Spain Validação de quatro definições de caso de aids em usuários de drogas injetáveis em Barcelona, Espanha - Paulo Sérgio C. Miranda; Andrés Marco; Joan Arthur Caylà; Hernando Galdós-Tangüis; Patricia García de Olalla (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 1998)
The objective of the study is to assess the sensitivity and specificity of four epidemiological AIDS-Case Definitions (CDC-87, CDC-93, Europe-93 and Revised Caracas) in HIV-infected intravenous drug users (IDU). The authors carried out a cross-sectional study with 136 IDUs, HIV-infected from a Men Penitentiary Center and from a drug addiction treatment center of Barcelona, Spain, between October/93 and April/94. A protocol, including demographic, clinical and laboratory variables was used by one doctor and the laboratory tests were done in the same institution. After that, the patients were classified in the four Epidemiological AIDS-Case Definitions used by this study. As gold standard we used the CD4 Cell Count (out point 200 or 14% CD4+). The number of AIDS cases varied between 31 and 84 according to the type of AIDS definition. The CDC-93 AIDS definition implied an increase of 170.9% in the number of cases in relation to CDC-87 AIDS-Case Definition. The sensitivities of the CDC-87, CDC-93, Europe-93 and Revised Caracas Epidemiological AIDS - Case Definitions were 34.2, 88.6, 45.6 and 56.9% while the specificities were 93.0, 75.4, 75.4 and 77.2%, respectively. The positive predictive values were between 72.0% (Europe-93) and 87.1% (CDC-87) and the negative predictive values were between 50.0% (Europe-93) and 82.7% (CDC-93). The authors concluded: the sensitivity and specificity of Caracas Revised Epidemiological AIDS-Case Definition was better than Europe-93 AIDS Case Definition. So this Definition can be very useful in countries and situations where the CD4 Cell Count is not available for technical or economical reasons. O objetivo do estudo é observar a sensibilidade e a especificidade de 4 definições epidemiológicas de Caso de Aids ("CDC-87", "CDC-93", "Europa-93"e "Caracas Revisada") em usuários de drogas (ilícitas) intravenosas, infectados pelo HIV/VIH. Os autores realizaram um estudo com 136 usuários, infectados pelo HIV/VIH, de um centro penitenciário para homens e de um centro de tratamento de usuários de drogas de Barcelona, Espanha, entre Outubro/1993 e Abril 1994. Um protocolo, incluindo variáveis demográficas, clínicas e laboratoriais, foi usado pelo mesmo médico e os testes laboratoriais, necessários à investigação, realizados na mesma instituição. Em seguida, os pacientes da amostra foram classificados nas 4 definições de Caso de Aids usados pelo estudo. Como padrão foi usada a contagem de CD4+. O número de casos de Aids variou entre 31 e 84 segundo a definição de Caso de aids utilizada. O uso de Definição CDC-93 implicou no aumento de 170,9% no número de casos com relação a Definição CDC-87. As sensibilidades das definições de Caso de Aids - CDC-87, CDC-93, Europa-93 e Caracas Revisada foram respectivamente, 34,2, 88,6, 45,6 e 56,9%, enquanto as especificidades foram, respectivamente, 93,0, 75,4, 75,4 e 77,2%. Os valores predictivos positivos estiveram entre 72,0% (Definição Europa-93) e 87,1% ("CDC-87") e os valores predictivos negativos se apresentaram entre 50,0% ("Europa-93) e 82,7% ("CDC-93"). Os autores concluíram que a Definição Epidemiológica de Caso de Aids "Caracas Revisada" apresentou melhor sensibilidade e especificidade que as apresentadas pela Definição de Caso de Aids "Europa-93". Por este motivo, a Definição de Caso "Caracas Revisada" pode ser útil em países e situação onde a contagem de células CD4+; por razões técnicas ou econômicas, não é disponível.